Bangladesh : Policy Options for Agriculture Insurance - World Bank Group (World Bank, Washington, DC, 2018)
Agriculture is a key sector in Bangladesh, but it is highly exposed to risks. While agriculture is a source of employment and livelihood for nearly one in two adults in Bangladesh and contributes about 16 percent to gross domestic product (GDP), it is highly exposed to natural hazards. In the past, the government of Bangladesh and development partners have provided substantial support to farmers in the aftermath of large disasters, but this approach has disadvantages in that support is not guaranteed to farmers and may be slow. Agricultural insurance offers the government a planned, fast, ex ante alternative to ad hoc disaster response, one that: (1) reduces the ex post fiscal burden on the government, (2) improves farmers’ resilience to shocks, and (3) supports the expansion of agricultural credit. International experience shows that government can play a variety of roles to support the responsible scale-up of agriculture insurance. The ministry of livestock and fisheries, and other key public and private sector stakeholders, the World Bank Group team has identified four potential types of agricultural insurance to offer in Bangladesh, all of which will require implementation through a partnership between the public and private sectors. The four types are dairy cattle insurance, aquaculture insurance, crop insurance, and fully subsidized agricultural insurance for the most vulnerable.